Pengaruh Bauran Pemasaran Terhadap Minat Beli Konsumen di Minimarket 212 Mart Karawaci Tangerang - Febriansyah Febriansyah; Dewi Reni (STES Islamic Village, 2020)
This study aims to determine the effect of marketing mix including product, price, location, and promotion partially and simultaneously on consumer buying interest in Minimarket 212 Mart Karawaci Tangerang.The method used in this research is descriptive quantitative method, which is included in the non-experimental quantitative method.The sampling technique in this study is the method of sampling random sampling, which is the technique of taking data sources that are chosen randomly.The results showed that the marketing mix includes Product (X1) and Price (X2) partially a significant positive effect on Consumer Purchase Interest in Minimarket 212 Mart Karawaci Tangerang.Whereas Location (X3) and Promotion (X4) partially did not have a significant positive effect on Consumer Purchase Interest in 212 Mart Karawaci Tangerang Minimarket. Simultaneously or together marketing mix variables which include Product (X1), Price (X2), Location (X3), and Promotion (X4) have a significant positive effect on Consumer Purchase Interest in Minimarket 212 Mart Karawaci Tangerang.